2010
DOI: 10.1186/cc9277
|View full text |Cite
|
Sign up to set email alerts
|

Year in review 2009: Critical Care - nephrology

Abstract: We summarize original research in the field of critical care nephrology accepted or published in 2009 in Critical Care or, when considered relevant or directly linked to this research, in other journals. Four main topics have been identified for a rapid overview: (a) post-surgical acute kidney injury (AKI); (b) timing of renal replacement therapy (RRT): different authors examined this critical issue of RRT in different settings (post-surgical patients, burned patients, and intensive care unit patients); (c) Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Third, we enrolled AKIN stage 3 acute cardiogenic shock patients only. It is possible that early-stage AKI patients requiring CRRT may receive a greater survival benefit from early dialysis [30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…Third, we enrolled AKIN stage 3 acute cardiogenic shock patients only. It is possible that early-stage AKI patients requiring CRRT may receive a greater survival benefit from early dialysis [30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…In the third category, articles using cystatin C as an early marker of ARF were examined. 55 Shlipak et al performed a meta-analysis of 16 studies (with 93710 participants) for whom standardized measurements of serum creatinine and cystatin C were available. They concluded that the use of cystatin C alone or in combination with creatinine strengthens the association between the GFR and the risks of death and end stage renal disease across diverse populations.…”
Section: Review Of Some Studies Examining Cystatin C As a Marker Of Rmentioning
confidence: 99%